Criticism of the Legislature's Approach to the Cost of Justice Services with a Look at the Principles of Fair Trial and UK Law - Pejman Mohamadi; Khalil Ahmadi; Milad Kianpouriannejad (پژوهشهای حقوقی)
The expansion of government activities and the development of administrative structures for the provision of public services and the fulfillment of the economic, cultural, and social rights of the people require that there be costs in return for the provision of these services; The judiciary is one of the public services to which the government owes and the belief that litigation is free should be discarded, but the costs of resolving disputes should not be such as to undermine the principles of fair trial or impose a financial burden. Impose a burden on plaintiffs. The provision of judicial services cannot and should not be sought only to generate revenue and neglect other purposes of litigation; Attention to goals such as reducing lawsuits, directing people to alternative institutions by gaining their trust in the judiciary, improving the quality and quantity of proceedings and rulings, and finally the satisfaction of the parties to the dispute and the outcome of the lawsuit, can provide the necessary income. The judiciary also guarantees its social goals, and in fact, with a comprehensive view of all goals, it is possible to provide a suitable criterion for determining the costs of litigation, and in this regard, legal principles should not be violated.The present research has been descriptive-analytical and with a documentary and study method, with an applied purpose, the effect of litigation costs on the principles of fair trial and a critique of the approach of the legislature and the judiciary towards this institution.